Скіфський курган 10 біля с. Мала Лепетиха у Нижньому Подніпров’ї - Євдокимов, Г.Л.; Данилко, Н.М.; Могилов, О.Д. (Археологія, 2012)
Публікуються матеріали кургану IV ст. до н. е. біля с. Мала Лепетиха на Херсонщині, що містили поховання дітей і воїнів. В 1992 г. Краснознаменская экспедиция Института археологии АН Украины под руководством Г.Л. Евдокимова исследовала курганный могильник у с. Малая Лепетиха на Херсонщине. В кургане 10, датирующемся IV в. до н. э., открыто как минимум два погребения воинов и несколько детских, образующих компактную группу. Центральная могила 6 была исследована раньше, возможно, Н.И. Веселовским в 1915—1916 гг. Погребения воинов 4 и 5 представляли катакомбы с дромосом и перпендикулярно расположенной погребальной камерой. Скелет в могиле 4 сопровождался более багатым инвентарем: однолезвийным мечем с золотой рукоятью, золотыми гривной, серьгой, браслетами и кольцом. Из оружия здесь были три колчанных набора, копье и дротики. Погребенного сопровождали заупокойная пища с ножом, котел, несколько наборов узды и амфора. Инвентарь из гробницы 5 был беднее: серебряная? гривна, золотые серьга и кольцо, один колчанный набор и дротик, котел, заупокойная пища с ножом и три амфоры. Детские погребения, совершенные в катакомбах, концентрировались в юго-западной части насыпи. Инвентарь их беден: бусы, браслет, серьга. The Krasnoznamyanska Expedition of the Institute of Archaeology of the AS of Ukraine headed by H.L. Yevdokymov studied the barrow cemetery near Mala Lepetykha Village in Kherson region in 1992. At least two warriors’ and several children’s burials creating a compact group were discovered in the barrow 10 dated to the 4th c. BC. The central tomb 6 was studied before, perhaps by N.I. Veselovskyi in 1915 and 1916. Warriors’ burials 4 and 5 were the catacombs with dromoi and a transversal funeral chamber. Grave goods near a skeleton in the grave 4 were richer: a singleblade sward with a golden hilt, a golden necklet, an earring, bracelets, and a ring. Arms here included three quiver sets, a spear and darts. A buried man was accompanied by the funeral food with a knife, a cauldron; several bridle sets and an amphora. The inventory in a tomb 5 was poorer: a silver(?) necklet, a golden earring and a ring, a quiver set and a dart, a cauldron, funeral food with a knife and three amphorae. Children’s graves made in catacombs were concentrated in the southwestern part of a mound. Their inventory is poor: beads, a bracelet, and a ring.